PROBLEMS, STRESS, SOCIAL SUPPORT, AND COPING STRATEGIES DURING THE COVID-19 PANDEMIC: CASE OF INTERNATIONAL COLLEGE STUDENTS IN INDONESIA - Defina, Defina; Rizkillah, Risda (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
Covid-19 has an impact on various areas of life in all walks of life. This condition also has an impact on students, especially in their education. This study aimed to analyze the effect of problems, stress levels, and social support on the coping strategies of international students in Indonesia during the Covid-19 pandemic. This study used a cross-sectional design with a quantitative approach—data were collected for two months, June-July 2020. The sample of this study was 88 foreign nationals who studied in Indonesia during the Covid-19 period. Findings, students had difficulty taking distance lectures because of weak signals and limited internet quota. Coping strategies used by this research sample in dealing with problems were spiritual support and rebuilding communication with family and friends online. The primary support in solving problems was family, especially parents. More than half of students fell into an average level of stress. The regression test results showed that income had a significant positive effect on coping strategies. This research implication suggests that the findings can be used to understand problems, stress levels, and coping strategies carried out by students during the Covid-19 pandemic to help stakeholders develop programs and policies related to learning problems during the Covid-19 pandemic.